Synthesis and exfoliation of a new layered mesoporous Zr-MOF comprising hexa- and dodecanuclear clusters as well as a small organic linker molecule - Leubner, Sebastian; Synnatschke, Kevin; Backes, Claudia (Journal of the American Chemical Society, 2020)
A new layered mesoporous Zr-MOF of composition [Zr30O20(OH)26(OAc)18L18] was synthesized by employing 5-acetamidoisophthalic acid (H2L) using acetic acid as the solvent. The new MOF, denoted as CAU-45, exhibits a honeycomb structure of stacked layers which comprise both hexa- and dodecanucelar zirconium clusters. Its structure was solved from submicrometer-sized crystals by continuous rotation electron diffraction (cRED). Liquid phase exfoliation and size selection were successfully performed on the material.
Gesehen am 03.11.2020